2019
DOI: 10.1016/j.neuroimage.2018.11.039
|View full text |Cite
|
Sign up to set email alerts
|

Neural activity in human visual cortex is transformed by learning real world size

Abstract: The way that our brain processes visual information is directly affected by our experience. Repeated exposure to a visual stimulus triggers experience-dependent plasticity in the visual cortex of many species. Humans also have the unique ability to acquire visual knowledge through instruction. We introduced human participants to the real-world size of previously unfamiliar species, and to the functional motion of novel tools, during a functional magnetic resonance imaging scan. Using machine learning, we compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 42 publications
(65 reference statements)
0
8
0
1
Order By: Relevance
“…Further, real-world size is detectable in early visual cortex, even when the common correlation between size and taxonomic category is removed (Coutanche & Koch, 2018). In a design that draws on a learning intervention, we have found that declaratively learning a novel item's real-world size can lead to changes in activity patterns in early visual cortex (Coutanche & Thompson-Schill, 2019). While being scanned with functional magnetic resonance imaging (fMRI), these participants viewed images of previously unfamiliar (and familiar) species, before and after learning the unfamiliar animals' real-world size through on-screen text.…”
Section: When Perceptual and Conceptual Knowledge Intersectmentioning
confidence: 87%
“…Further, real-world size is detectable in early visual cortex, even when the common correlation between size and taxonomic category is removed (Coutanche & Koch, 2018). In a design that draws on a learning intervention, we have found that declaratively learning a novel item's real-world size can lead to changes in activity patterns in early visual cortex (Coutanche & Thompson-Schill, 2019). While being scanned with functional magnetic resonance imaging (fMRI), these participants viewed images of previously unfamiliar (and familiar) species, before and after learning the unfamiliar animals' real-world size through on-screen text.…”
Section: When Perceptual and Conceptual Knowledge Intersectmentioning
confidence: 87%
“…Therefore, although a real car and a toy car share similar visual appearances, actions on these two objects are completely different ( 8 ). Further, the feature of objects’ real-world size also provides important information for high-level cognitive processes, such as attention ( 33 ), numerical perceptions ( 34 ), and semantic knowledge ( 35 ). In short, our finding that the feature of objects’ real-world size served as an axis of object space thus may greatly expand our understanding of object recognition from the angle of vision for perception to a novel viewpoint of vision for action.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, although a real car and a toy car share similar visual appearances, actions on these two objects are completely different 5 . Further, the feature of objects' real-world size also provides important information for highlevel cognitive processes, such as attention 31 , numerical perceptions 32 , and semantic knowledge 33 . In short, our finding that the feature of objects' real-world size served as an axis of object space thus may greatly expand our understanding of object recognition from the angle of vision for perception to a novel viewpoint of vision for action.…”
Section: Discussionmentioning
confidence: 99%